Reforming accounting to support the shift towards a sustainable financial system - Nihel Chabrak (Journal of Capital Markets Studies (JCMS), 2018)
Purpose - Considering the growing importance of finance in shaping corporate and human activities, the purpose of this paper is to focus on the United Nations Environment Programme (UNEP) Inquiry into the Design of a Sustainable Financial System that aims to align the financial system with sustainable development, with a focus on environmental aspects. Following the inquiry call for better disclosure approaches of material information on the "sustainability impacts" of the financial system as one of the areas of improvement to move toward a sustainable financial system, the author argues for a reform of the accounting model to better reflect the compliance of businesses with "quality of growth" imperatives. Design/methodology/approach - The paper rests on the entity theory of Littleton (1934). Findings - The new accounting model requires creating a new equity capital account for the entity that is separate from the shareholders equity account. Valuation as well as other related issues on the functioning of this account is briefly explored in the paper. The reform also requires entrusting the responsibility of answering questions related to valuation, capital maintenance and income distribution to the board of directors that should be composed of representatives of the different capitals which have accrued, temporarily or indefinitely, to the business firm. Research limitations/implications - This paper calls researchers to explore the theoretical avenues proposed in the paper to develop the model in practice. Practical implications - The implementation of this reform requires a regulatory reform and the redesign of the economic coordination mechanisms which could be challenging in practice. Social implications - The accounting model proposed in the paper contributes to a new quality of growth, which is a growth based on well-being and inclusiveness. Originality/value - The paper draws on the UNEP framework, which has not been investigated in other research studies.
Keywords: 330; Accounting; Entity; Financial system; Littleton; Quality of growth; UNEP inquiry